Оцінка хромосомних порушень в соматичних клітинах хворих на рак щитоподібної залози, що постраждали від Чорнобильської аварії - Неумержицька, Л.В.; Клименко, С.В.; Коваль, Г.М.; Вербиленко, Р.М.; Шкарупа, В.Н. (Фактори експериментальної еволюції організмів, 2013)
Aims. Research level and spectrum of chromosomal aberrations in peripheral blood lymphocytes of patients with thyroid cancer, which were last ionizing radiation due to the Chernobyl accident. Methods. Сytogenetic analysis of human lymphocytes. Results. Cytogenetic studies of peripheral blood lymphocytes of patients with thyroid cancer. This group of patients previously exposed to radiation. The frequency of chromosomal aberrations in peripheral blood lymphocytes of patients with higher levels of spontaneous and significantly higher than the control group.

Key words: thyroid cancer, chromosome aberrations, radiation.